Sistem Pendukung Keputusan Pemilihan Supplier Terbaik Pada PT. Madjin Crumb Rubber Factory Menggunakan Metode Waspas - Amir, Faisal; Utomo, Dito Putro (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Madjin Crumb Rubber Factory is a company in the field of rubber processing with a number of clients and a high level of rubber processing production, the existence of suppliers is very important, therefore the selection of suppliers is very influential on the results and quality of the rubber processed. PT. Madjin Crumb Rubber Factory does not produce it themselves but has to look for other suppliers or suppliers who have stock of goods in accordance with the company's request. The first step in selecting the best supplier is choosing a supplier by doing a selection first. PT. Madjin Crumb Rubber Factory has a manual system and is assessed subjectively. The purpose of the subjective here is more to the situation where the company chooses suppliers based on proximity alone or in other words the selection of suppliers at this time is still random or there is no reference, so that the results obtained by clients and management are sometimes unsatisfactory, therefore a support system is designed. decisions to make the selection more effective and accurate. The decision support system is made by applying the WASPAS method. The system created will provide recommendations for selecting the best supplier at PT. Madjin Crumb Rubber Factory, involving five criteria, namely price, production, quality, service and delivery time, then there are eight alternatives given by PT. Madjin Crumb Rubber Factory. By using Microsoft Visual Studio 2008 for the design of a decision support system and Microsoft Access 2010 as a database. This research can provide convenience to the PT. Madjin Crumb Rubber Factory in making decisions on choosing the best supplier and providing objective and accurate results in making the best supplier selection decision.